(untitled) (Tribhuvan University Journal of Microbiology, 2018)
Objectives: The study was carried out in Kathmandu Model Hospital, Kathmandu with the aim of in- vitro biofilm detection among uropathogens and its correlation with antibiotic resistance. Methods: Uropathogens (n=234) were isolated, and identified with standard microbiological techniques and further subjected to Modified Congo Red Agar Method for the biofilm detection in-vitro; antimicrobial susceptibility testing (10 antibiotics) was performed by Modified Kirby Bauer disc diffusion method. The MIC and MBEC values of Levofloxacin were determined by agar dilution for planktonic forms and by microdilution method for biofilm phase respectively. Results: Among 234 urine isolates, 134(57%) were positive for in-vitro biofilm production and 88(37.6%) were multidrug resistant (MDR). E. coli was the predominant biofilm forming uropathogens. The incidence of biofilm producers was found to be independent of age-wise, gender wise and indoor-outdoor distribution of patients. The association between biofilm production and multidrug resistance among uropathogens was found statistically non-significant (p-value>0.05). The MBEC values of biofilm phase of growth were found to be greater than the MIC values for their planktonic counterparts. The MBEC values ranged from 4 to more than1024 μg/ml whereas the MIC values ranged from 0.003-16 μg/ml. Conclusion: The results of the present study suggest that biofilm detection is a critical step to fight against biofilm-involved infections. However, further studies are needed for the development of effective preventive and treatment strategies of biofilm associated UTIs to avoid recurrence and persistence.